L-1 Robustness of Computed Torque Method for Robot Manipulators - Kim, Jung Hoon; Oh, Yonghwan; Hur, Sung-moon (2018 IEEE INTERNATIONAL CONFERENCE ON ROBOTICS AND AUTOMATION (ICRA), 2018)
This paper revisits computed torque method for robot manipulators and aims at developing its new framework based on the L-1 robustness, in which the L-infinity norm together with its induced norm is employed to characterize model uncertainties and a performance measure. More precisely, we consider the L-1 robust stability and performance for a given robot manipulator with a computed torque controller. We first show that the modelling errors in the computed torque method can be divided into an exogenous disturbance and a multiplicative model uncertainty, which are bounded in terms of the L-infinity norm and its induced norm, respectively. It is next shown that the robot manipulator with the computed torque controller can be equivalently represented by an interconnection of a continuous-time linear time-invariant (LTI) nominal plant and a stabilizing controller together with the L-infinity-induced norm bounded model uncertainty. Based on the interconnected representation, the L(1 )robust stability condition and an upper bound of the L-1 performance against the exogenous disturbance with respect to all model uncertainties in a class of a bounded L-infinity-induced norm are dealt with by using the small-gain theorem. Finally, the effectiveness of the theoretical results is demonstrated through some experiment results.